(untitled) (Research, Society and Development, 2021)
Analyze the scientific evidence on stress factors in nursing professionals who work in the Intensive Care Unit. It deals with a bibliographic review of the integrative literature review method, carried out in the months of November and December 2020. The search was carried out, through the Platform - VHL, using the databases (LILACS), (BDENF), and through Google Scholar Portal, adhering to the descriptors: “Stress”, “Nursing Professionals”, “Intensive Care Unit”, combined with the operator “Boolean”. Intensive Care Units demonstrate that nursing professionals who work in these environments face high levels of stress. There is a very close relationship between daily exposure to stressors related to the exhausting and tiring environment and stress. Health professionals, particularly those who work in Intensive Care Units (ICUs), are in a vulnerable situation for the development of stress conditions. In a ICU, the work routine is marked by variability, uncertainty and risk, factors that can trigger stress for many professionals; in addition, excessive noise, the relationship with the team and the relationship with family members and patients can be additional sources of stress in this context. The nurse and the hospital must recognize the stressors that are present at work and look for individual and collective coping mechanisms and strategies to reduce the occurrence of professional stress.